Rancang Bangun Sistem Monitoring Detak Jantung (Electrocardiogram) Suhu Tubuh Denyut Nadi Berbasis Nodemcu Esp32 Dan Esp8266 Dengan Menggunakan Wearable Device - Cahyo Purnomo, Dandy; Sandi, Efri; Yusro, Muhammad (PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA, 2022)
The purpose of this research is to create a heart rate monitoring system (Electrocardiogram) pulse body temperature based on NodeMCU ESP32 and ESP8266 using a Wearable Device for use by military/TNI soldiers during exercise such as pushups, squat jumps, bending, and others related to the distance. not far, not too heavy, and not in the water through the GOIOT monitoring website which can then be used by trainers, teachers, or trainers from a military/TNI soldier in monitoring. This research was conducted using the research and development method developed by Brog & Gall. The basic principle that is characteristic of the research and development method is the 4-stage Brog & Gall Model, namely: the analysis stage, the design stage, the development stage, and the testing stage. The system performance of the heart rate sensor (Electrocardiogram) with the AD-8232 ECG module while exercising can read the physiological parameters of the ECG heart rate from a voltage of 0.1 to a voltage of 5.0 (mV). Temperature sensor Dallas DS18b20 Thermal Digital Sensor while exercising can read the human body temperature from 0°C to 100°C. MAX30100 pulse sensor, can read the human pulse when exercising from 0 bpm to 160 bpm. The performance of the system can work with a distance of 1 meter to 30 meters in an open environment without intervening with others (without any obstacles). Can be used with a full incharge of the battery from 8.27 Volts for 4 hours non-stop, that is, until the battery remains 7 Volts. The implication is that it can be used to detect only three data, namely heart rate (Electrocardiogram) body temperature pulse to then be forwarded to monitoring devices positioned at operators who need the data such as doctors or people who understand readings from heart rate (Electrocardiogram) body temperature pulse rate only.